Inhibition of ZERO‐BK by PKC is involved in carbachol‐induced enhancement of rat colon smooth muscle motility. Issue 7 (28th February 2018) - Xin, F.; Huang, H.; Liu, P.; Ren, J.; Zhang, S.; Cheng, Y.; Wang, W.
Abstract: Background: Muscarinic acetylcholine receptor (mAChR) activation is an important factor to enhance the motility of gastrointestinal (GI) smooth muscle. Large conductance Ca 2+ ‐activated potassium (BK) channels are widely expressed in GI smooth muscle. Roles of BK in carbachol (a mAChR agonist) induced enhancement of GI motility and the molecular mechanisms remains unknown and were investigated in this study. Methods: Colonic smooth muscle (CSM) strip was perfused to record motility in vitro. The patch‐clamp technique was used to record BK currents. RT‐PCR was used to detect the expression of BK channels in rat CSM tissues. Two different types BK channels were constructed in HEK293 cells to investigate the regulation mechanism. Paired t tests were set with a P < .05 regarded as significant. Key Results: Carbachol enhanced CSM contraction through M3 receptor (M3 R) were attenuated by IbTX, an inhibitor of BK. Carbachol inhibited BK currents in CSM cells and Go6983, an inhibitor of protein kinase C (PKC), reversed the effect. PKC activator, phorbol 12‐myristate 13‐acetate (PMA), inhibited BK currents. Two types of BK channels (ZERO‐BK and STREX‐BK) were detected in CSM. ZERO‐ but not STREX‐BK channels expressed in HEK293 cells were inhibited by PMA. Conclusion: Our results provide strong evidence that inhibition of ZERO‐BK but not STREX‐BK channels via PKC pathway is involved in the enhancement of CSM motility by mAChR activation. Besides the activation of BK by an increase in intracellular calcium, inhibition of BK played an important role in GI motility regulation during mAChR activation. Abstract : BK channels were involved in basic and carbachol‐induced contraction regulation of GI strips. Only ZERO‐BK channels were inhibited by PKC which took part in carbachol‐induced motility enhancement in rat CSM.